Modelling the Predictors of Social Media Marketing on Consumer Buying Behavior in Malaysia - Borhan, Halimahton; Mohamed, Rozita Naina; Rusli, Mohd Saifullah; Othman, Azhana; Marmaya, Najihah Hanisah; Md Razak, Mohamad Idham; Ridzuan, Abdul Rahim (Information Management and Business Review, 2024)
Despite the rapid increase in internet and mobile users in Malaysia, the growth of online purchases through social media platforms has not kept pace with this broader digital trend. This study investigates the key predictors that influence consumer buying behavior through social media marketing, with a specific focus on the roles of Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) of these platforms. Employing a quantitative cross-sectional research design, data were collected from 115 respondents in Malaysia who have experience making online purchases via mobile applications. The study also examines variations in consumer experiences based on demographic factors, including age, gender, education level, and geographic region. The findings indicate that both PEOU and PU are significant predictors that shape consumer buying behavior on social media platforms. This research provides valuable insights for marketers seeking to enhance the effectiveness of their social media marketing strategies. By better understanding the factors driving consumer behavior in the Malaysian market, businesses can design more targeted and personalized campaigns for specific consumer segments, ultimately improving their competitive advantage in this digital landscape.